Synopsis of subfamily Haplogleniinae Newman, 1853 in China (Neuroptera: Ascalaphidae) - Zhang, Jie; Sun, Mingxia; Wang, Xinli (Zootaxa, 2015)
A synopsis of the subfamily Haplogleniinae Newman, 1853 (Neuroptera: Ascalaphidae) is presented. One new synonyms is proposed. Protidricerus palliventralis Yang, 1999 syn.n. is a junior synonym of Protidricerus elwesii (McLachlan, 1891). Two genera and eight species are redescribed and illustrated, and keys to the genera and species are presented.